Enhanced Detection of Early Hepatocellular Carcinoma by Serum SELDI-TOF Proteomic Signature Combined with Alpha-Fetoprotein Marker - Chen, Lei; Ho, David W. Y.; Lee, Nikki P. Y.; Sun, Stella; Lam, Brian; Wong, Kwong-Fai; Yi, Xin; Lau, George K.; Ng, Eddy W. Y.; Poon, Terence C. W.; Lai, Paul B. S.; Cai, Zongwei; et al. (Annals of surgical oncology, 2010)
Background Biomarkers for accurate diagnosis of early hepatocellular carcinoma (HCC) are limited in number and clinical validation. We applied SELDI-TOF-MS ProteinChip technology to identify serum profile for distinguishing HCC and liver cirrhosis (LC) and to compare the accuracy of SELDI-TOF-MS profile and alpha-fetoprotein (AFP) level in HCC diagnosis. Patients and Methods Serum samples were obtained from 120 HCC and 120 LC patients for biomarker discovery and validation studies. ProteinChip technology was employed for generating SELDI-TOF proteomic features and analyzing serum proteins/peptides. Results A diagnostic model was established by CART algorithm, which is based on 5 proteomic peaks with m / z values at 3324, 3994, 4665, 4795, and 5152. In the training set, the CART algorithm could differentiate HCC from LC subjects with a sensitivity and specificity of 98% and 95%, respectively. The results were assessed in blind validation using separate cohorts of 60 HCC and 60 LC patients, with an accuracy of 83% for HCC and 92% for LC patients. The diagnostic odd ratio (DOR) indicated that SELDI-TOF proteomic signature could achieve better diagnostic performance than serum AFP level at a cutoff of 20 ng/mL (AFP 20 ) (92.72 vs 9.11), particularly superior for early-stage HCC (87% vs 54%). Importantly, a combined use of both tests could enhance the detection of HCC (sensitivity, 95%; specificity, 98%; DOR, 931). Conclusion Serum SELDI-TOF proteomic signature, alone or in combination with AFP marker, promises to be a good tool for early diagnosis and/screening of HCC in at-risk population with liver cirrhosis.